Investigation of hydrophobicity variations in hBN-Embedded SiO2-Na2O-B2O3-Bi2O3-ZnO-F glass-ceramic coating systems - Gucuyener, Yaren; Nermin, Elvan; Ozturk, Gamze; Daloglu, Sinan; Karaahmet, Oguz; Cicek, Bugra (ELSEVIER, 2025)
This study investigates the effect of hexagonal boron nitride (hBN) additives on the hydrophobicity and surface morphology of glass-ceramic coatings (GCCs). A precursor glass (PG) system composed of SiO2-Na2O-B2O3Bi2O3-ZnO-F was milled with varying hBN concentrations (0 %, 0.5 %, 1.0 %, 3.0 %, and 5.0 %). The resulting slurries were wet-sprayed onto a metal substrate and subsequently devitrified at 810 degrees C for 4.5 min. X-ray Diffraction (XRD) analysis of the coatings confirmed the successful incorporation of hBN crystallinity within the glassy matrix. Non-contact optical profilometry (NCOP) revealed that surface roughness (Ra) increased from 1.58 mu m to 2.89 mu m, while topographic mapping showed an increase in surface height variation (Delta h) from 20 mu m to 45 mu m as hBN content increased. Scanning Electron Microscopy (SEM) further corroborated these results, demonstrating a progressive increase in surface roughness with higher hBN content. The unmodified GCC exhibited a smooth and uniform morphology, whereas coatings with hBN, particularly at 5 wt%, displayed a rougher, more heterogeneous surface topography. These observed microstructural changes closely aligned with NCOP and contact angle measurements. Contact angle (CA) analysis demonstrated a notable enhancement in hydrophobicity, with values increasing from 27.27 degrees for the unmodified GCC to 90.95 degrees at the highest hBN concentration. These findings collectively demonstrate that incorporating hBN into GCCs effectively enhances surface roughness and hydrophobicity, thereby offering significant potential for various industrial applications.
Keywords: Hexagonal boron nitride; Glass-ceramic coating; Contact angle; Hydrophobicity; Micro-roughness; HEXAGONAL BORON-NITRIDE; SUPERHYDROPHOBIC SURFACES; DIELECTRIC-PROPERTIES; LOTUS; FILM; ZNO; Chemistry; Physics